Penerapan Risk Management Framework untuk Pelaksanaan Proyek Alih Daya Sistem Informasi di BPK RI - Andika Arif Sukrawan; Wing Wahyu Winarno (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Badan Pemeriksa Keuangan Republik Indonesia (BPK) as one of the government agencies or the public sector since 2002 until the present project has been realized in the form of outsourcing of information systems application software. Some examples of the failure of IT projects including IT outsourcing has demonstrated the importance of the role of risk management. One framework that can be used by organizations in implementing risk management approach is to use the Project Management Body of Knowledge (PMBOK). Stages of risk management contained in the PMBOK and IT outsourcing is discussed in depth in this study. The results of the application of risk management suggests that the absence of risk management plans and risk factor analysis of user needs, the risk of a protracted workmanship, and the risk of vendor staff qualifications are a high risk probability and impact. Development of risk response and risk monitoring and control is an important step after high risks identified. The results of the application is expected to be a guideline for the implementation of BPK in IT outsourcing, so that the benefits of IT outsourcing to precisely target.